2020
DOI: 10.1039/d0cc01176b
|View full text |Cite
|
Sign up to set email alerts
|

A halide perovskite as a catalyst to simultaneously achieve efficient photocatalytic CO2 reduction and methanol oxidation

Abstract: We have firstly demonstrated the photocatalytic utilization of a halide perovskite for combining reduction of CO2 with selective oxidation of methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…For example, Wu et al integrated photocatalytic CO 2 reduction with oxidative organic transformation using CdSe/ CdS QDs [192], thus enabling the full utilization of photoexcited electrons and holes to simultaneously produce CO and valueadded chemical (pinacol); Zhang et al designed an efficient InP-In 2 O 3 p-n junction photocatalytic system [193], which combined CO 2 reduction with the photooxidation reaction of tetrahydroisoquinoline to obtain high value-added gas and liquid chemicals, respectively. In very recent, Lu et al demonstrated that the CsPbBr 3 could simultaneously achieve efficient photocatalytic CO 2 reduction and methanol oxidation [194]. These strategies provide idea alternatives to the sacrificial agents.…”
Section: Utilization Of Sacrificial Agentsmentioning
confidence: 99%
“…For example, Wu et al integrated photocatalytic CO 2 reduction with oxidative organic transformation using CdSe/ CdS QDs [192], thus enabling the full utilization of photoexcited electrons and holes to simultaneously produce CO and valueadded chemical (pinacol); Zhang et al designed an efficient InP-In 2 O 3 p-n junction photocatalytic system [193], which combined CO 2 reduction with the photooxidation reaction of tetrahydroisoquinoline to obtain high value-added gas and liquid chemicals, respectively. In very recent, Lu et al demonstrated that the CsPbBr 3 could simultaneously achieve efficient photocatalytic CO 2 reduction and methanol oxidation [194]. These strategies provide idea alternatives to the sacrificial agents.…”
Section: Utilization Of Sacrificial Agentsmentioning
confidence: 99%
“…Artificial photosynthesis is presently receiving intense attention because of its great potential to meet the global demand for sustainable development, [1] accomplishing the recycling of CO 2 by employing clean sunlight energy to drive the reduction reaction of CO 2 to generate chemical energy over photocatalysts [2] . In this technology, apart from CO 2 reduction integrated with meaningful chemical reactions, [3, 4] the photocatalysis of CO 2 reduction coupled with water (H 2 O) oxidation is considered to be a dream reaction for generating solar fuels or value‐added chemical feedstocks and O 2 gas [5] . To date, various semiconductors have been exploited as photocatalysts to achieve CO 2 reduction and H 2 O oxidation simultaneously [6–8] .…”
Section: Figurementioning
confidence: 99%
“…Remarkably, they have employed hexafluorobutyl methacrylate to improve NC’s stability and dispersity in an aqueous medium. Then, in this class of materials, Zhang and coworkers reported Co-doped CsPbBr 3 embedded in the matrix of Cs 4 PbBr 6 (a surface protector) [ 66 ]. The reason behind such protection of Cs 4 PbBr 6 was to improve the stability of ligand-free CsPbBr 3 perovskite.…”
Section: Lead Halide Perovskites For Photocatalytic Co 2mentioning
confidence: 99%